EVALUASI KINERJA KUD BUKIT MANUNGGAL PADA BAGIAN PEMASARAN TANDAN BUAH SEGAR (TBS) KELAPA SAWIT DI KECAMATAN SUNGAI BAHAR - Rezeki, Sri; Kasiono, Kasiono (SJEE (Scientific Journals of Economic Education), 2022)
The aims of this study were (1) to find out the performance of the marketing division of KUD Bukit Manunggal, Sungai Bahar sub-district, and (2) to find out how to apply alternative strategies through SWOT analysis to improve the performance of the marketing division of KUD Bukit Manunggal, Sungai Bahar sub-district. The type of research in this research is descriptive qualitative research. Data collection techniques in this study were observation, interviews, and documentation. The data analysis technique used in this study is a SWOT analysis technique with a qualitative approach, which consists of Strengths, Weaknesses, Opportunities and Threaths.The results showed that (1) the performance of KUD Bukit Manunggal's marketing division had not been fully implemented optimally. This conclusion is based on the performance of KUD Bukit Manunggal management who are always optimal in selling FFB, but on the other hand, they do not yet have a clear marketing strategy so it can also be said that the marketing division is not carrying out its functions as it should, and (2) There are 3 alternatives strategies that can be applied in developing the marketing division obtained from a combination of Strengths and Opportunities (SO), namely (a) Maximizing the potential for FFB sales by opening RAM under the auspices of KUD. Through the opening of RAM under the auspices of KUD, it is hoped that it will be able to reach a wider membership so that it can increase the effectiveness of KUD Bukit Manunggal's marketing performance, (b) Improve the performance of administrators to reach other villages that do not yet have KUD. By improving the performance of the management through training, the management, especially the marketing department, will be able to develop their performance to reach villages that do not yet have a KUD to join the Bukit Manunggal KUD, and (c) Utilize the independence of the KUD to explore other villages. The KUD's freedom to sell products to any factory that is suitable and easily accessible can be used by the KUD to build trust and gather members from other villages that have not yet joined the KUD.Keywords: KUD Performance Evaluation, Marketing